Educação de jovens e adultos: práticas pedagógicas e uso da internet - Faccioni, Paulo (2017)
The present work has the theme of Young and Adult Education: pedagogical practices and the use of the Internet. It arose from the interest of investigating the pedagogical practice carried out with the use of the information that circulates through the Internet in the Education of Young and Adults. The central concepts of research are based on authors who deal with the Education of Young and Adult; of pedagogical practice; the use of the internet in education and the research works that have been developed in this field. For this, it was listed as the central question of the research was listed: How has the use of the internet in pedagogical practice in the Basic Education of Young and Adults in CEEBJA - Araucária? The research has as a research site the CEEBJA - Araucária, located in the municipality of Araucária / PR. Its general objective is to analyze the pedagogical practices with the use of data and information from the internet for learning in Young and Adult Education in the CEEBJA - Araucária. The research is based on the quantitative and qualitative approach and, for its realization, the following research instruments were used: semistructured interview with teachers and students; questionnaire, with open and closed questions, applied to the students of CEEBJA - Araucária. The results of the research showed that teachers and students use the information circulating on the Internet for teaching and learning and that the pedagogical practice of the teachers who work in CEEBJA - Araucária turns to the overcoming of the educational model focused on teaching by teacher. But this pedagogical practice is still far from the liberating educational conception due to lack of structure, time for planning, continuous formation among other factors